Reframing the Human-Fish in the Edo and Meiji Periods: Eroticism, Taxidermy, Oracles, and Modernity - Castiglioni, Andrea (Journal of Religion in Japan, 2023)
This article explores the history of a marine zoo-anthropomorphic hybrid, the human-fish (ningyo), within the socioreligious mindscape of Japan from the second half of the seventeenth to the end of the nineteenth century. Because of the interspecific anatomy attributed to them, ningyo have always been addressed from heterogeneous perspectives (religious, literary, political, erotic, scientific) and have thus been subject to continuous hermeneutic oscillations between the fringes and the centers of human/nonhuman networks. Focusing on this bidirectional process, the present study aims to shed light on the phenomenon of the ningyo, taking into account the material culture (taxidermic items, printed talismans), practices (sideshows, public exhibitions), and social actors (itinerant ritualists, scientists, politicians) that conceptually informed and anatomically reified this liminal marine creature.